1999
DOI: 10.1021/cm980676h
|View full text |Cite
|
Sign up to set email alerts
|

Optical Second Harmonic Generation in Achiral Bis(n-alkylamino)dicyanoquinodimethanes:  Alkyl Chain Length as the Design Element

Abstract: Chain length of substituted n-alkyl groups is proposed to be a convenient design element for the generation of noncentrosymmetric crystal lattices of interest in optical second harmonic generation (SHG). Powder studies on 7,7-Bis(n-alkylamino)-8,8-dicyanoquinodimethanes indicate that moderate solid-state optical SHG is obtained when the alkyl chains are of length 4, 5, and 6, and no detectable SHG occurs when the chains are of length 0, 3, 7, 8, and 12. The significant role of the intermediate alkyl chain leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…We have been investigating diaminodicyanoquinodimethanes (DADQ), because of their quadratic nonlinear optical applications, [15,16] and more recently due to the enhanced solid state fluorescence exhibited by some of the derivatives (eg., BMPDQ in Scheme 1). [17] We have now observed spontaneous resolution through helical organization in crystals of a related molecule decorated with a variety of ionic and potential hydrogen bonding sites.…”
Section: Introductionmentioning
confidence: 99%
“…We have been investigating diaminodicyanoquinodimethanes (DADQ), because of their quadratic nonlinear optical applications, [15,16] and more recently due to the enhanced solid state fluorescence exhibited by some of the derivatives (eg., BMPDQ in Scheme 1). [17] We have now observed spontaneous resolution through helical organization in crystals of a related molecule decorated with a variety of ionic and potential hydrogen bonding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to probe further, we have calculated the Hyper Rayleigh Scattering (HRS) (b HRS ), using the coupled perturbed Hartree-Fock (CPHF) scheme using Eq. (12). The CPHF scheme predicted the static response properties (b HRS ) of the titled compound are shown in Table 2.…”
Section: Isomermentioning
confidence: 99%
“…The subsequent extension of this conjugated system is found to increase the hyperpolarizability value [9]. However, studies have shown that an appropriate design of the alkyl chain length attached to the p conjugated system can enhance the NLO activity [11][12][13]. In addition, it is also observed that a moderate chain length is sufficient to stimulate strong NLO activity.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Fluorescence switching in molecular systems have been achieved by photoactivated reactions [17] and thermochromism. [21] Molecular materials based on the diaminodicyanoquinodimethane (DADQ) system [22] that produce strong optical second harmonic generation [12,23] as well as enhanced fluorescence in the solid state [24] have been developed in our laboratory.R ecently,a morphous nanoparticles of aD ADQ derivative were fabricated and transformed to the crystalline state with different fluorescence emission, by solvent vapor fuming. In none of the cases was either awell-characterized amorphous phase and bistability established, or extensive amorphous-crystalline cycling exclusively by thermal processing demonstrated.…”
mentioning
confidence: 99%
“…[25] However,r eversible transformation, preferably thermally induced, is required to realize aviable PCM. Them olecule has the zwitterionic structure typical of DADQs, [23,28] with ad ihedral twist angle (q)o f about 46.78 8 between the diaminomethylene moiety and the benzenoid ring. Quenching the melts produces amorphous materials at ambient temperatures,which can then be transformed back to the crystalline state by heating to temperatures (T c )ofabout 70 8 8Ca nd cooling slowly;t his reversible transformation can be repeated several times.M ost significantly,t he bistable amorphous/crystalline forms exhibit strikingly different fluorescence emission responses,i nt erms of intensity (weak/ strong) as well as color (cyan/blue).…”
mentioning
confidence: 99%